ROS-responsive dimeric prodrug-based nanomedicine targeted therapy for gastric cancer - Jiachi Ma; Yuzhong Chen; Wanqing Liang; Lei Li; Jun Du; Chengwu Pan; Chensong Zhang (Taylor & Francis Group, 2021)
Gastric cancer (GC) remains a major public health problem. Ursolic acid (UA) is reported to be effective in inhibiting GC; however, its low solubility and poor biocompatibility have greatly hindered its clinical application. Herein, an innovative reactive oxygen species (ROS)-sensitive UA dimeric prodrug is developed by coupling two UA molecules via a ROS-cleavable linkage, which can self-assemble into stable nanoparticles in the presence of surfactant. This new UA-based delivery system comprises the following major components: (I) dimeric prodrug inner core that can achieve high drug-loading (55%, w/w) and undergo rapid and selective conversion into intact drug molecules in response to ROS; (II) a polyethylene glycol (PEG) shell to improve colloid stability and extend blood circulation, and (III) surface-modified internalizing RGD (iRGD) to increase tumor targeting. Enhancement of the antitumor effect of this delivery system was demonstrated against GC tumors in vitro and in vivo. This novel approach offers the potential for clinical applications of UA.